Tietze's Extension Theorem for Intuitionistic Fuzzy $ζ-$Basically Disconnected Spaces in Katetov-Tong's Sense - S. Sharmila; I. Arockiarani (International Journal of Mathematics And its Applications, 2015)
In this paper we initiate the concept of $ζ-$basically disconnectedness in intuitionistic fuzzy topological spaces. We also apply these notions of $ζ-$basically disconnectedness to analyse and prove Tietze extension theorem.